THE ROLE OF CULTURE IN THE NEW RUSSIAN FOREIGN POLICY - A. V. Shestopal; N. V. Litvak (Концепт: философия, религия, культура, 2017)
The article examines the formulation and development of the role and significance of culture in international relations in the context of the Foreign Policy Concepts of the Russian Federation after the Soviet Union collapse. Based on the content of five of these concepts, a consistent growth of attention to this factor in international relations is demonstrated. The origins of this phenomenon are also analyzed. Firstly, the essence of modern international relations between the capitalist states in the aftermath of the “Cold War” remains an all-out competition, instead of a constructive cooperation, a partnership wished by the leadership of the new Russia after 1991. Secondly, the parity in weapons of mass destruction, achieved during the confrontation between the USA and the USSR and still holding back from a new global conflict, forced to transfer this competition into the cultural field, making information wars its priority. It was also promoted by scientific and technical achievements including electronic media and communications. The victory in such a war is not a capture of the hostile terrain, but it’s a cultural leadership resulting in the control over all of its resources through educational systems, values and culture. Therefore, in the Russian Foreign Policy Concepts appeared a theses that “a global competition for the first time in the modern history is acquiring a civilizational dimension which suggests competition between different value systems and development models”; that “The reaction to the prospect of the loss by the historic West of its monopoly on the globalization processes is reflected, in particular, in the inertia of the political and psychological attitude on the” containment “of Russia”, and that “The strategy of unilateral actions destabilize the international situation … (and) leads to increased tension in relations between civilizations; the onslaught of globalization, cultural identity is exposed to the vast majority of countries and peoples”.